CLUSTER ANALYSIS AND RADIATION MONITORING OF ENVIRONMENT - Getmanets, О.; Nekos, А.; Гетманець, O.; Некос, A.; Пеліхатий, М. (Київський національний університет імені Тараса Шевченка, 2019)
Building a background radiation field on the ground on the basis of measurement data taken at a finite number of points is one of the most important tasks of radiation monitoring. The aim of the work: to study the possibility of applying cluster analysis for the tasks of radiation monitoring of the environment. Cluster analysis is a multidimensional statistical analysis. Its main purpose is to split the set of objects under study (observation points) into homogeneous groups or clusters, that is, the task of classifying data and identifying the corresponding structure in them is solved. Methods of research: the measurements of the power of the ambient dose of continuous X-ray and gamma radiation on the terrain by using the MKS05 dosimeter "TERRA-0"; processing of the obtained data by cluster analysis methods using the computer program "Statistics-10", wherein each cluster point is characterized by three coordinates: two coordinates on the ground and the power of the ambient dose of radiation at a given point; Euclidean distance was chosen as the distance between two points. Results: after processing data using various clustering methods: the method of Complete Linkage, the method of Weighted pair-group average and the Ward's method, it was found that the results of the analysis practically coincide with each other, that proves the reliability of the application of cluster analysis for the tasks of radiation monitoring of the environment and mapping of radiation pollution. Conclusions: the concept of a "radiation cluster" was first formulated in this work, combining coordinates on a plane with an ambient dose rate;the possibility of using cluster analysis to construct a map of radiation pollution of the environment has been proved by sequential projectionfrom more connected to less connected radiation clusters onto the plane of the controlled zone. In this sense, cluster analysis is similar to the operator approach to the construction of the radiation field. For further research, it is of some interest to study the issues of integration of cluster analysis with geographic information systems.

Побудова поля радіаційного фону на місцевості на підставі даних вимірювань, що були проведені в кінцевому числі точок, – одне з найважливіших завдань радіаційного моніторингу. Мета роботи: дослідження можливості застосування кластерного аналізу для завдань радіаційного моніторингу довкілля. Кластерний аналіз є багатовимірним статистичним аналізом. Його головне призначення – розбиття множини досліджуваних об'єктів (точок спостережень) на однорідні групи або кластери, тобто вирішується завдання класифікації даних і виявлення в них певної структури. Методи досліджень: вимірювання потужності амбієнтної дози безперервного рентгенівського і гамма-випромінювання на місцевості за допомогою дозиметра МКС-05 "ТЕРРА-0", обробка отриманих даних методами кластерного аналізу із застосуванням комп'ютерної програми "Statistics-10", при цьому кожна точка кластера характеризувалася трьома координатами: двома координатами на місцевості й потужністю амбієнтної дози випромінювання в цій точці; відстанню між двома точками була обрана евклідова відстань. Результати: після обробки даних із застосуванням різних способів кластеризації: методу ближнього сусіда, методу зваженого попарного середнього і методу Варда було встановлено, що результати аналізу якісно практично збігаються між собою, це доводить достовірність застосування кластерного аналізу для задач радіаційного моніторингу місцевості й побудови карт радіаційного забруднення. Висновки: у роботі вперше сформульовано поняття "радіаційного кластера", що об'єднує координати на площині з потужністю амбієнтної дози; доведена можливість застосування кластерного аналізу для побудови карти радіаційного забруднення довкілля шляхом послідовного проектування від більш пов'язаних до менш пов'язаних радіаційних кластерів на площину контрольованої зони. У цьому сенсі кластерний аналіз аналогічний операторному підходу до побудови поля радіації. Для подальших досліджень становить певний інтерес вивчення питань інтеграції кластерного аналізу з геоінформаційними системами.
КЛАСТЕРНИЙ АНАЛІЗ І РАДІАЦІЙНИЙ МОНІТОРИНГ ДОВКІЛЛЯ
Keywords: radiation monitoring; X-ray and gamma radiation; cluster analysis; радіаційний моніторинг; рентгенівське та гамма-випромінювання; кластерний аналіз